Essays in economics of child protection - Petra Gram Cavalca (University of Copenhagen, Department of Economics, 2021)
The thesis consists of three self-contained chapters. The chapters can be read independent of each other and each chapter is followed by a bibliography and an appendix. They each cast light on a different aspect of how we, as a society, manage the responsibility of helping children who do not thrive in their own home, and to what extent we succeed in helping these children find their way in life. Thank you for your interest.
Keywords: 330; Kinderschutz; Familienökonomik